2021
DOI: 10.1155/2021/8878703
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A Supplementation Coverage and Ocular Signs among Children Aged 6–59 Months in Aleta Chuko Woreda, Sidama Zone, Southern Ethiopia

Abstract: Background. Periodic vitamin A supplementation to children is a cost-effective strategy to avert vitamin A deficiency. However, few pieces of evidence are available about the coverage of vitamin A supplementation at the community level in the study area. Therefore, the aim of this study was to assess vitamin A supplementation coverage and prevalence of ocular signs of vitamin A deficiency among children aged 6–59 months. Methods. Community-based cross-sectional study design was conducted using a two-stage stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
1
8
2
Order By: Relevance
“…The finding has supported another study conducted in Ethiopia and elsewhere in SSA (14,38). The variation could be associated with a lack of awareness and paying less attention among young mothers (30,39). This might become a huge loss when we consider that teenage pregnancy is common in Ethiopia (40).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The finding has supported another study conducted in Ethiopia and elsewhere in SSA (14,38). The variation could be associated with a lack of awareness and paying less attention among young mothers (30,39). This might become a huge loss when we consider that teenage pregnancy is common in Ethiopia (40).…”
Section: Discussionsupporting
confidence: 78%
“…This might be related to the culture of Ethiopia where after delivery a mother exposes herself late during the postpartum period. A study conducted somewhere showed a different association (14,39). Nevertheless, the health extension workers and the women development armies should pay attention to the good uptake of VAS among lower-aged children.…”
Section: Discussionmentioning
confidence: 99%
“…Although regarded as an important public health nutritional intervention, the usefulness of the dated vitamin A policy (that encourages routine practice of universal VAS) is being increasingly questioned,19 47–50 with calls for more nuanced and sustainable alternatives. It is true that the coverage of VAS, even in the recent past, was found to influence the prevalence of VAD-related health problems like childhood blindness in some affected nations 51 52. But there are also concerns (in India and elsewhere) that the routine practice of administrating massive vitamin A doses indiscriminately has outlived its intended usefulness and that its further continuation may actually put children at risk of developing vitamin A toxicity 19 47–50 53–55.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the uptake of vitamin A supplementation is influenced by socio-economic, demographic, and geographical factors. Such as ANC follow-up [ 26 , 27 ] parental educational status [ 12 , 28 , 29 ], maternal knowledge [ 2 , 30 ], monthly income and wealth index [ 2 , 12 , 29 ], maternal employment status [ 27 , 29 ], media exposure [ 27 29 ], age of the child [ 12 , 28 – 31 ], place of delivery [ 27 ], and distance to the health institution [ 30 , 32 ].…”
Section: Introductionmentioning
confidence: 99%